2005
DOI: 10.1016/j.molcel.2005.08.036
|View full text |Cite
|
Sign up to set email alerts
|

An Electrostatic Steering Mechanism of Cdc42 Recognition by Wiskott-Aldrich Syndrome Proteins

Abstract: The specific and rapid formation of protein complexes is essential for diverse cellular processes such as remodeling of actin filaments in response to the interaction between Rho GTPases and the Wiskott-Aldrich syndrome proteins (WASp and N-WASp). Although Cdc42, TC10, and other members of the Rho family have been implicated in binding to and activating the WAS proteins, the exact nature of such a protein-protein recognition process has remained obscure. Here, we describe a mechanism that ensures rapid and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
164
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(182 citation statements)
references
References 49 publications
13
164
2
Order By: Relevance
“…The results indicated that the stabilities of the two proteins are rather similar. Also, the x-ray crystal structure of the edited RhoQ protein compared with the previously reported WT RhoQ protein structure (Hemsath et al, 2005) indicated that there are no changes in the global or local structural folds (Fig. 4 B).…”
Section: Protein Structure Of Edited Rhoqmentioning
confidence: 57%
“…The results indicated that the stabilities of the two proteins are rather similar. Also, the x-ray crystal structure of the edited RhoQ protein compared with the previously reported WT RhoQ protein structure (Hemsath et al, 2005) indicated that there are no changes in the global or local structural folds (Fig. 4 B).…”
Section: Protein Structure Of Edited Rhoqmentioning
confidence: 57%
“…It would therefore be predicted that components of the Cdo complex would cluster at sites of active Ncad ligation. To test this notion, Ncad ectodomain-coated microspheres were allowed to settle onto adherent NIH 3T3 cells that transiently expressed fluorescently tagged forms of Ncad, Cdo, JLP, Bnip-2, or the Cdc42-binding domain of N-Wasp (wGBD), which inter- acts specifically with active, GTP-bound Cdc42 (30). Cadherincoated beads attach to cells via cognate cellular cadherins, and additional cellular proteins that cluster at these sites of adhesion can be visualized as a fluorescent signal surrounding the bead (31)(32)(33).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the N-WASP domain does not localize to the plasma membrane when expressed in yeast, and it cannot restore signaling when used to replace the Ste20 BR domain (S. Takahashi and P. M. Pryciak, unpublished data). Second, the polybasic domain of N-WASP has been proposed to interact transiently with acidic residues in Cdc42 and thereby accelerate CRIB-Cdc42 binding by "electrostatic steering" (Hemsath et al, 2005). In contrast, it seems unlikely that the yeast BR domains need to directly contact Cdc42, given the ability of PH domains to substitute for their function.…”
Section: Synergistic Protein-protein and Protein-membrane Interactionsmentioning
confidence: 99%